2000
DOI: 10.1557/proc-609-a6.2
|View full text |Cite
|
Sign up to set email alerts
|

Gas Phase and Surface Kinetic Processes in Hot-Wire Chemical Vapor Deposition

Abstract: One- and two-dimensional numerical simulations have been used to determine the parameters critical to high rate growth of high quality polycrystalline silicon via hot-wire chemical vapor deposition at silane partial pressures of 1-70 mTorr and a wire temperature of 2000°C. The Direct Simulation Monte Carlo method [1] was used, including gas-phase chemistry relevant for growth. Model predictions agree both qualitatively and quantitatively with experimental measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…There have been a number of recent reports [3][4][5][6] of the distribution of wire-desorbed radicals, following the early report by Doyle et al 7 Experiments conducted using similar detection schemes, such as vacuum ultraviolet photoionization mass spectrometry, have shown quite different results in some cases. 4,5 Whether these differences are due to the different histories of the wire used or differences in the reactor condition ͑e.g., amorphous silicon-coated walls͒ is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…There have been a number of recent reports [3][4][5][6] of the distribution of wire-desorbed radicals, following the early report by Doyle et al 7 Experiments conducted using similar detection schemes, such as vacuum ultraviolet photoionization mass spectrometry, have shown quite different results in some cases. 4,5 Whether these differences are due to the different histories of the wire used or differences in the reactor condition ͑e.g., amorphous silicon-coated walls͒ is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the SiH 3 homogeneous reaction SiH 2 is created, which at higher pressures may polymerize further to Si 3 H 4 . Holt et al [554] have performed Monte Carlo simulations to study gas phase and kinetic processes in HWCVD. They showed that under the conditions for obtaining device quality material SiH 3 is the most abundant species at the substrate.…”
Section: Ixd Deposition Modelmentioning
confidence: 99%
“…The silane (SiH 4 ), used as source gas, induces the formation of silicide (WSi x ) at the surface of the tungsten (W) wire employed as catalyzer. Moreover, the radical desorption kinetics from the filament profoundly change with silicide formation [6,7]. The aging of the catalyzer implies a low reproducibility of the deposited material quality.…”
Section: Introductionmentioning
confidence: 99%